Register Perkebunan Karet Afdeling Karanggadungan Kecamatan Ngargoyoso Kabupaten Karanganyar Dan Implementasinya Pada Pembelajaran Bahasa Indonesia Di Sma Kelas X - Simarmata, Happy Try Haryawati, Drs.Agus Budi Wahyudi, M.Hum (2017)
This study reviews the Register of Rubber Plantation ambodgien Karanggadungan Ngargoyoso District of Karanganyar And Implementation On Learning Indonesian in Sma Class X. This research aims 1) to describe the shape of a rubber plantation registers karanggadungan subdistrict section Ngargoyoso Karanganyar district 2) describe the meaning of section rubber plantation sub-district karanggadungan Ngargoyoso Karanganyar district 3) describes its lementation in Indonesian language learning in Class X. Sma type of research is to study the problems this is descriptive qualitative research because the purpose of this study provides an analysis of rubber plantations Cambodgien Karanggadungan registers. The technique used to collect data that refer techniques and note. Data analysis technique used is the method agih and unified method. The results of the research found the register of rubber plantation afdeling karanggadungan based on the form there are two words, three verbs, seven nouns, five verb phrases, nine noun phrases, three clauses, one sentence and nineteen acronyms.Its implementation in Indonesian language learning to learners in class X SMA competence standards Indonesian communicate with similar levels and basic competencies 1.1 semenjana Listening to understand verbal information in a social context. Keywords: departmen, estates, register